2012
DOI: 10.1538/expanim.61.139
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt of Cryopreservation of Mouse Embryos at the ACTREC Laboratory Animal Facility in India

Abstract: Abstract:Cryopreservation is the long-term storage of viable cells/tissue in liquid nitrogen. The present study was conducted to freeze 8-cell-to morula-stage mouse embryos from the ACTREC Laboratory Animal Facility using a "slow freezing and fast revival" method. In all, 4,088 embryos were collected from 495 donor female mice of ten different strains. An average recovery of 8 embryos per donor mouse were recorded. Of the 4,088 embryos, 3,946 embryos of normal morphology were frozen in 173 straws. They were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…There are some reports of significant differences between strains in the survival rate of cryopreserved embryos using the frozen method [31,34]. In Experiment 2, the survival rates for the * There were no significant differences among any groups (P > 0.01).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are some reports of significant differences between strains in the survival rate of cryopreserved embryos using the frozen method [31,34]. In Experiment 2, the survival rates for the * There were no significant differences among any groups (P > 0.01).…”
Section: Discussionmentioning
confidence: 95%
“…Although several methods are available for cryopreservation of early mouse embryos, including freezing [35] and vitrification [28], the survival rate of early embryos after cryopreservation tends to be higher for the vitrification technique with little difference among strains [18] compared to freezing [29][30][31]34]. Embryo development of multiple strains after cryopreservation also tends to be better with vitrification than with freezing [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment 1, we vitrified BDF1 strain 2‐cell stage mouse embryos, which are known to have a high cryotolerance . The results clearly showed that a cryopreservation test using embryos with a high cryotolerance cannot manifest potential difference in performance of the methods.…”
Section: Discussionmentioning
confidence: 98%
“…ACTREC laboratory animal facility have mouse embryo cryo repository for in-house usage. W e have already cryopreserved some of our valuable strains (Thorat and Ingle, 2012). For embryo collection, we need to euthanize more numbers of donor females and require significant time and efforts.…”
Section: Safeguard the Valuable Strainsmentioning
confidence: 99%